2024
DOI: 10.1021/jacs.4c03994
|View full text |Cite
|
Sign up to set email alerts
|

Darobactin Substrate Engineering and Computation Show Radical Stability Governs Ether versus C–C Bond Formation

Austin M. Woodard,
Francesca Peccati,
Claudio D. Navo
et al.

Abstract: The Gram-negative selective antibiotic darobactin A has attracted interest owing to its intriguing fused bicyclic structure and unique targeting of the outer membrane protein BamA. Darobactin, a ribosomally synthesized and post-translationally modified peptide (RiPP), is produced by a radical S-adenosyl methionine (rSAM)-dependent enzyme (DarE) and contains one ether and one C–C cross-link. Herein, we analyze the substrate tolerance of DarE and describe an underlying catalytic principle of the enzyme. These ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 82 publications
0
0
0
Order By: Relevance
“…Further, if the third amino acid is serine (Ser) (Ω1-X2-S3), serine −OH is oxidized to aldehyde. This further supports the hypothesis proposed by Woodard et al that the radical stability of the intermediates drives the C–C cross-linking . Later, Ma et al identified several divergent darobactins, including photorhaptin A (Figure B) …”
Section: Biosynthesis Of Darobactinssupporting
confidence: 84%
See 2 more Smart Citations
“…Further, if the third amino acid is serine (Ser) (Ω1-X2-S3), serine −OH is oxidized to aldehyde. This further supports the hypothesis proposed by Woodard et al that the radical stability of the intermediates drives the C–C cross-linking . Later, Ma et al identified several divergent darobactins, including photorhaptin A (Figure B) …”
Section: Biosynthesis Of Darobactinssupporting
confidence: 84%
“…The two proposed mechanisms differ in the position of installation of the initial hydroxy radical. Pathway A is further supported by Woodard et al…”
Section: Biosynthesis Of Darobactinsmentioning
confidence: 63%
See 1 more Smart Citation